Synthesis of active ingredients for medicines by genetically modified plants - Luthar, Zlata (Anali PAZU, 2022)
In recent years, the findings in clinical trials of recombinant medicines derived from genetically modified (GM) plants boomed. For these purposes, some numerous attempts to increase expression of antigens for the treatment of infectious viral and bacterial diseases have been successfully carried out. In recent times, research has focused on optimizing the synthesis and extraction of antigens for the treatment of autoimmune and genetic diseases. It is also considered in the direction of the synthesis of the antigens for the treatment of tropical diseases. The development is focused on the use of medicines with the consumption of fresh plant material (especially in veterinary medicine). Component vaccines derived from GM plants can arouse a stronger immune response and immunological memory for a longer period. Their acquisition is related to lower production costs. Despite all the research and achievements, none of the medicines obtained by GM plants is present on the market. To achieve that it will be necessary to eliminate the problems associated with the production, use and particularly problems related to biosafety and the general public's perception of GM plants.
Keywords: genetically modified plants; synthesis; recombinant proteins; antigens; healing; immune response; immunological memory